"Citizen Journalism" in the Syrian Uprising: Problematizing Western Narratives in a Local Context. Issue 4 (20th October 2014) - Al-Ghazzi, Omar
Abstract: This article analyzes the term 'citizen journalism' against the backdrop of the Arab uprisings in order to show how it overlooks the local context of digital media practices. The first part examines videos emanating from Syria to illustrate how they blur the lines between acts of witnessing, reporting, and lobbying, as well as between professional and amateur productions, and civic and violent intentions. The second part highlights the genealogies of citizenship and journalism in an Arab context and cautions against assumptions about their universality. The article argues that the oscillation of Western narratives between hopes about digital media's role in democratization in the Arab World and fears about their use in terrorism circumscribe the theorization of digital media practices.